PROCEDURES FOR APPARATUS MUSCLE TESTING - ESSENCE AND PERFORMANCE - Stefka P. Mindova; Irina Karaganova; Denitza Vassileva (Peytchinski Publishing, 2019)
The Muscle Test is an important tool for all healthcare team members who are committed to restoring the patient's physical health and a fundamental element in identifying motor disorders. The outcomes obtained from this test are the basis for choosing an optimal therapeutic approach, a strategy for rehabilitation and tracking of the recovery process in dynamics. The lack of objectivity and quantitative data for comparison in muscle strength measurement in manual testing creates prerequisites for inaccuracies and subjective judgment on the part of the examiner. This has given rise to the search for additional tools to support standard muscle assessment methods, such as apparatus muscle testing. It provides more accurate, quantitative and objective assessments and creates a prerequisite for refining the muscle test and preserving it in an electronic database accessible to a team of specialists.